2004
DOI: 10.1159/000077727
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Antibodies for Clinical Applications in Cancer

Abstract: The ‘magic bullet’ concept predicted over a century ago that antibodies would be used to target cancer therapy. Since then initial problems that were related to specificity, purity and immungenicity of antibody-based reagents have slowly been overcome due to developments in technology and increased knowledge. As a result, antibodies are in use for many clinical applications and now comprise the second largest category of medicines in clinical development after vaccines. For antibody-based cancer therapeutics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 30 publications
0
24
1
2
Order By: Relevance
“…Monovalent antibodies have faster circulatory clearance and weaker antigen binding than IgGs, resulting in lower tumor uptake and therapeutic potential but reduced systemic toxicity. It has also been suggested that they have the ability to localize more rapidly into tumor deposits (37,38). However, our results show that there was no physical barrier to localization and penetration of IgG (MW 150 kDa) into and through hepatic tumor deposits of all sizes.…”
Section: Discussioncontrasting
confidence: 47%
“…Monovalent antibodies have faster circulatory clearance and weaker antigen binding than IgGs, resulting in lower tumor uptake and therapeutic potential but reduced systemic toxicity. It has also been suggested that they have the ability to localize more rapidly into tumor deposits (37,38). However, our results show that there was no physical barrier to localization and penetration of IgG (MW 150 kDa) into and through hepatic tumor deposits of all sizes.…”
Section: Discussioncontrasting
confidence: 47%
“…Bispecific adapters with a CEA-binding domain should untarget adenovirus vectors from normal tissues and retarget them to CEA-positive tumors. MFE-23, a single-chain antibody with high affinity for CEA, is currently in phase I studies both as an imaging agent for radioimmunoguided surgery and as a tumor-targeting agent for antibody-directed enzyme prodrug therapy (20)(21)(22). To retarget CEA-positive cells, MFE-23 has been fused to sCAR to form sCAR-MFE, a bispecific transductional reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody engineering permits the design of new antibodybased proteins that can potentially address the shortcomings of intact antibodies as cancer therapeutics (1). One approach has been to produce the minimal antibody binding site in the form of a single-chain Fv (sFv), comprising the heavy and light chain variable domains of an antibody, joined by an appropriate linker peptide (2,3).…”
mentioning
confidence: 99%